2014
DOI: 10.1002/hlca.201400074
|View full text |Cite
|
Sign up to set email alerts
|

PN Bond Cleavage during the Insertion of Carbon Fragments into PIIIN Bonds in Bis(diphenylphosphino) Amines

Abstract: The reaction of tertiary amine functionalized phosphines with aromatic and aliphatic aldehydes gives insertion of carbon fragments into the P III ÀN bonds or P III ÀN bond cleavage. The reaction of bis(diphenylphosphino) amines, 1a -1c, with two equiv. of aldehydes in toluene afforded the P III ÀN bond inserted products, 2a -4a, 4b -6b, and 3c -5c, in moderate-to-good yield. The products were characterized by IR, . This arises from several distinct advantages presented by PÀN containing ligands. Soft/hard ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In a recent study, Biricik et al have shown that the reaction of the DPPA derivatives 75 – 77 with aldehydes (2 equiv) led, after P–N bond cleavage, to the formation of their respective insertion products of general formula (Ph 2 PO)­CH­(R)­NH­[ x , y -(MeO) 2 C 6 H 3 ], ( x , y = 3,5; 2,5; 2,4; R = H, Me, Ph, C 6 H 4 OMe- p , C 6 H 4 Cl- p ) …”
Section: Oxygen-based Functionalizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Biricik et al have shown that the reaction of the DPPA derivatives 75 – 77 with aldehydes (2 equiv) led, after P–N bond cleavage, to the formation of their respective insertion products of general formula (Ph 2 PO)­CH­(R)­NH­[ x , y -(MeO) 2 C 6 H 3 ], ( x , y = 3,5; 2,5; 2,4; R = H, Me, Ph, C 6 H 4 OMe- p , C 6 H 4 Cl- p ) …”
Section: Oxygen-based Functionalizationsmentioning
confidence: 99%
“…Relevant structural parameters are reported in Table 7. 67 3.1.4. Other N-Functional Groups Containing an R− O−R′ Moiety.…”
Section: Chemical Reviewsmentioning
confidence: 99%